Investigation of Medicinal Plants Utilized by Indigenous People in Saptari District of Madhesh Province, Nepal - Das, Bishnu Dev; Sah, Prativa Kumari Sah; Sardar, Amrita; Paudyal, Som Prasad; Paudel, Niroj (BMC Journal of Scientific Research, 2024)
The study has been carried out to investigate the traditional knowledge of ethnomedicine among the indigenous people of Saptari district, Nepal. The study has identified 83 plant species from 46 plant families overall. Out of the total number of plant species, 41 were domesticated and 42 were wild. Herbs account for the largest percentage of the 83 species of plants, followed by trees (31.32%), shrubs (20.48%), and climbers (6.024%). The Fabaceae family includes up to nine plant species that are used medicinally. Malvaceae, Moraceae, Solanaceae, and Lamiaceae all have four species apiece. From the Amaranthaceae, Apocynaceae, Apiaceae, and Poaceae plant families, three plant species were noted. From the Rutaceae, Amaryllidaceae, Araceae, Meliaceae, Brassicaceae, Zingiberaceae, Euphorbiaceae, Myrtaceae, and Combretaceae plant families, two species are noted. The remaining families each represent a different type of plant. The plant species that have been collected are renowned for their ability to treat ailments like tonsillitis, elephantiasis, tonsillitis, Alzheimer's, Parkinson's, colds, arthritis, gastritis, gonorrhea, diarrhea, dysentery, jaundice, and leprosy. Plant species from the list are reported to be effective in treating a variety of conditions, including arthritis, cancer, diabetes, asthma, bronchitis, leprosy, tuberculosis, intestinal worms, anemia, syphilis, skin disease, and others